PERBANDINGAN PENGARUH PROBLEM-BASED LEARNING DAN SIMULATION-BASED EDUCATION TERHADAP KEMAMPUAN PSIKOMOTOR BASIC LIFE SUPPORT MAHASISWA KEPERAWATAN - Bambang Sudono Dwi Saputro; Retna Puspitasari; Sutanta Sutanta (Jurnal Cakrawala Keperawatan, 2024)
Background: Initial treatment efforts in patients with cardiac arrest are Basic Life Support (BLS). PBL is a method used to cultivate clinical reasoning in nurse education programs. Problem Based Learning (PBL) is able to improve the skills and learning outcomes of students compared to conventional methods. SBE is the environment that suitable to practice student skills, Simulation Based Education (SBE) also used to improve students' critical thinking, problem solving and teach psychomotor skills. Comparative evaluation of the useof Problem Based Learning (PBL) and Simulation Based Education (SBE) on psychomotor abilities is a consideration for the use of both methods to improve psychomotor abilities. Purpose: This study aims to compare the effect of PBL and SBE on the psychomotor abilities of BLS nursing students. Methods: This research is an experimental study with a design quasi experiment with comparison group. The total respondents were selected with each respondent in each group using the technique simple random sampling. Psychomotor ability data was measured by the BLS psychomotor ability observation sheet which was adopted from guideline AHA. Descriptive statistics, test wilxocon and testman whitney used as analysis. Results: The median value before being given PBL was 4 and the psychomotor ability after giving PBL was 11. The median value before being given SBE was 3 and psychomotor ability after giving SBE was 14. There was an effect of giving PBL (p= 0.001) and SBE (p= 0.001) on the psychomotor ability of BLS. There is a significant difference between PBL and SBE on the psychomotor abilities of BLS with the PBL and SBE methods with a score of (p=0.018). Conclusion: PBL and SBE are able to improve the psychomotor abilities of BLS. Although both learning methods can improve BLS psychomotor abilities, the SBE learning method shows better performance than the PBL method.